Endoscopic biliary therapy in the era of bariatric surgery. Issue 2 (24th February 2021) - Martin, Harry; El Menabawey, Tareq; Webster, Orla; Parisinos, Constantinos; Chapman, Michael; Pereira, Stephen P; Johnson, Gavin; Webster, George
Abstract : There is an increasing demand and availability of bariatric surgery, with a range of procedures performed, some leading to altered upper gastrointestinal anatomy. The patient population undergoing bariatric surgery is also at increased risk of gallstones and biliary stone disease. Endoscopy (ie, endoscopic retrograde cholangiopancreatography) is the cornerstone of management of biliary stone disease, but may be challenging after bariatric surgery. In this review the endoscopic, surgery assisted, or percutaneous options that may be considered are discussed, based on the details of surgical anatomy and available expertise.